LABORATORY BIOMARKERS FOR ANKYLOSING SPONDYLITIS - E. N. Aleksandrova; A. A. Novikov (Научно-практическая ревматология)
Ankylosing spondylitis (AS) is a chronic inflammatory disease from a group of spondyloarthritis (SpA), which is characterized by lesions of the sacroiliac joints and spine with the common involvement of entheses and peripheral joints in the pathological process. Advances in modern laboratory medicine have contributed to a substantial expansion of the range of pathogenetic, diagnostic, and prognostic biomarkers of AS. As of now, there are key pathogenetic biomarkers of AS (therapeutic targets), which include tumor necrosis factor-α (TNF-α), interleukin 17 (IL-17), and IL-23. Among the laboratory diagnostic and prognostic biomarkers, HLA-B27 and C-reactive protein are of the greatest value in clinical practice; the former for the early diagnosis of the disease and the latter for the assessment of disease activity, the risk of radiographic progression and the efficiency of therapy. Anti-CD74 antibodies are a new biomarker that has high sensitivity and specificity values in diagnosing axial SpA at an early stage. A number of laboratory biomarkers, including calprotectin, matrix metalloproteinase-3 (MMP-3), vascular endothelial growth factor, Dickkopf-1 (Dkk-1), and C-terminal telopeptide of type II collagen (CTX II) do not well reflect disease activity, but may predict progressive structural changes in the spine and sacroiliac joints in AS. Blood calprotectin level monitoring allows the effective prediction of a response to therapy with TNF inhibitors and anti-IL-17А monoclonal antibodies. The prospects for the laboratory diagnosis of AS are associated with the clinical validation of candidate biomarkers during large-scale prospective cohort studies and with a search for new proteomic, transcriptomic and genomic markers, by using innovative molecular and cellular technologies.